Effect of Dietary Inclusion of Moringa Oleifera Leaf Meal on Carcass and Meat Quality Characteristics of Broilers - L, Murali. (Indian Journal of Animal Nutrition, 2020)
The present study was carried out to study the effect of dietary inclusion of Moringa oleifera leaf meal (MOLM) on meat quality characteristics of broilers. Day old broilers of 180 numbers were distributed randomly to six dietary groups each with five replicates of 6 birdsÂ and were maintained under uniform management conditions. Experimental diets were prepared by incorporation of Moringa oleifera leaf meal (MOLM) at 0% (T1; negative control), control + Vit-E,Se,Vit-C(T2;positive control), 1.5% (T3), 3.0%(T4), 4.5% (T5) and 6.0% (T6)Â levels. All the rations were made iso-caloric and iso-nitrogenous. The carcass traits like live weight, carcass weight and ready to cook yield were higher (p<0.01) in birds fed with 3.0% MOLM group. On other hand, inclusion of MOLM from 0 to 6.0% in diet had no effect (p>0.05) on dressing percentage, liver heart, gizzard and giblet weights and proximate composition of meat The meat quality parameters of broilers revealed that inclusion of MOLM up to 6% level had no effect on pH, Extract Release Volume (ERV), Water Holding Capacity (WHC) and sensory evaluation of the meat except colour of the meat. Colour of the meat was decreased (p<0.01) at 6.0% level of MOLM present in the diet. Results of this study indicate that MOLM can safely be incorporated up to 6% level in diets of broilers without effecting carcass quality for economic benefit.